2003
DOI: 10.1001/archsurg.138.9.987
|View full text |Cite
|
Sign up to set email alerts
|

Core Needle Biopsy as a Diagnostic Tool to Differentiate Phyllodes Tumor From Fibroadenoma

Abstract: Hypothesis: Core needle biopsy is a useful diagnostic tool in differentiating phyllodes tumor from fibroadenoma. Design: The radiology database was queried for patients who underwent core needle biopsies of fibroepithelial lesions that raised the possibility of phyllodes tumor. These diagnoses were then compared with the final pathological diagnoses after surgical excision. Setting: The data were gathered from the Comprehensive Breast Center, Columbia Presbyterian Medical Center, a tertiary care, university-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
2
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 10 publications
8
75
2
5
Order By: Relevance
“…Choi (12) reported that among 129 patients having undergone preoperative CNB diagnosis, 104 were verified by postoperative pathology, yielding an accuracy rate of 80.6%, similar to the results of Bode et al (11). In addition, Komenaka et al (22) and Ward et al (17) reported accurate CNB diagnostic rates of 76.0% and 63.0%. Although these four reports achieved diagnosis rates above 50%, most studies reported accuracies below this line (15,19,20,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 53%
“…Choi (12) reported that among 129 patients having undergone preoperative CNB diagnosis, 104 were verified by postoperative pathology, yielding an accuracy rate of 80.6%, similar to the results of Bode et al (11). In addition, Komenaka et al (22) and Ward et al (17) reported accurate CNB diagnostic rates of 76.0% and 63.0%. Although these four reports achieved diagnosis rates above 50%, most studies reported accuracies below this line (15,19,20,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 53%
“…Core biopsy represents the best modality for preoperative diagnosis with a sensitivity of 99%, negative predictive value and positive predictive value 93% and 83%, respectively. 24 Core biopsy using 14-gauge needle enables to provide an extra-architectural information provided by histology compared with cytology. 25 In the case of ulcerated lesion, wedge biopsy is needed instead.…”
Section: Diagnosismentioning
confidence: 99%
“…Although CNB can provide high negative and positive predictive values, accurate diagnosis based on a limited sample from CNBs can sometimes be challenging for fibroepithelial neoplasms because of the heterogeneity and overlapping features in these lesions. 9,10,26 At times, fibroadenoma can show moderate cellularity, mimicking PTs, and PTs may have heterogeneous components similar to benign fibroadenoma. Many studies have shown the need for biomarkers, especially Ki-67, in addition to the histologic features of these lesions for more accurate preoperative evaluation.…”
Section: Role Of Core Needle Biopsy In Diagnosis Of Fibroepithelial Tmentioning
confidence: 99%